The metabolic cost of nesting: body condition and blood parameters of Caiman crocodilus and Melanosuchus niger in Central Amazonia - Barão-Nóbrega, José António Lemos (2018)
Although nesting ecology is well studied in several crocodilian species, it is not known how nest attendance influences physiology and body condition of nesting females. In this study, we describe body condition and serum biochemical values of nesting female, non-nesting female and male spectacled caiman (Caiman crocodilus) and black caiman (Melanosuchus niger) in two areas of Central Amazonia. We also evaluated the effect of nest age and nest distance to water on body condition and blood parameters of nesting females. Body condition and plasmatic concentrations of glucose, triglycerides, lactate and uric acid of nesting females were significantly different from those of non-nesting females and males in C. crocodilus, but not in M. niger. Our study also demonstrated that nest age and distance to water had a negative effect on female body condition in C. crocodilus, but not in M. niger. Female C. crocodilus attending older nests or nests built further away from permanent water bodies tended to have lower body condition. Our results demonstrate that the nesting strategy of C. crocodilus has a metabolic cost associated with nest attendance for nesting females, which appear to depend on accumulated energetic reserves during nest attendance. In contrast, nest attendance had little effect on the physiology of female M. niger. © 2017, The Author(s).